Smart Detector Device for Rooms and Offices - Mohamad Helmi Bin Abd Halim, Mohamad Helmi (2009)
Energy crisis is one of the major topics that have been discussed recently. So, in order to overcome those problems, development must be made. In this thesis, I will try to at least help people not waste their time on tracking person and try to prevent energy waste in term of electricity usage.